STRATEGI PENGEMBANGAN EKOWISATA TAMAN MARGASATWA MANGKANG KOTA SEMARANG - Pradana, Sandy Harselan; Larasati, Endang; Mustam, Muhammad (Journal of Public Policy and Management Review, 2013)
The tourism industry is often seen as the answer to deal with economic problems. Economic hardship and unequal economic development will be considered resolved by the tourism industry. However, it should be realized that these activities also have a negative impact, one of which is environmental. Form the aspect of tourism activities and environmental sustainability is ecotourism. Wildlife Areas Mangkang Semarang City is a place that combines the concept of wildlife conservation education and the concept of tourism.This study used a qualitative descriptive method. The locus of this research in the area of Semarang Mangkang Wildlife Areas and Focus on Strategic Development of Ecotourism Wildlife Areas Semarang. The methods used to collect the data, namely: Documentation, Observation, Interview. Sources of data in this study using primary data and secondary data. Efforts to address the problem and the purpose of the study used the theory of strategic management using SWOT analysis tool, as well as the litmus test.Preformance of this research there were 5 observed phenomena, namely: Conditions Mangkang Wildlife Areas, Strategic Environmental, supporting factors and obstacles, Strategic Issues and Formulating Strategic Programs. The results of this study indicate that the Development Strategy of the Government of Semarang city is going well, but there are still some shortcomings such as Human Resources as a constraint, while the layout of the park is very strategic Wildlife Mangkang is one factor driving.